Evaluation of protection induced by a dengue virus serotype 2 envelope domain III protein scaffold/DNA vaccine in non-human primates. Issue 30 (24th June 2016) - McBurney, Sean P.; Sunshine, Justine E.; Gabriel, Sarah; Huynh, Jeremy P.; Sutton, William F.; Fuller, Deborah H.; Haigwood, Nancy L.; Messer, William B.
Highlights: Proof of principle of a protein scaffold/DNA based dengue virus vaccine. Highly immunogenic in rhesus macaques. Conferred protection against viremia on challenge. Abstract: We describe the preclinical development of a dengue virus vaccine targeting the dengue virus serotype 2 (DENV2) envelope domain III (EDIII). This study provides proof-of-principle that a dengue EDIII protein scaffold/DNA vaccine can protect against dengue challenge. The dengue vaccine (EDIII-E2) is composed of both a protein particle and a DNA expression plasmid delivered simultaneously via intramuscular injection (protein) and gene gun (DNA) into rhesus macaques. The protein component can contain a maximum of 60 copies of EDIII presented on a multimeric scaffold of Geobacillus stearothermophilus E2 proteins. The DNA component is composed of the EDIII portion of the envelope gene cloned into an expression plasmid. The EDIII-E2 vaccine elicited robust antibody responses to DENV2, with neutralizing antibody responses detectable following the first boost and reaching titers of greater than 1:100, 000 following the second and final boost. Vaccinated and naïve groups of macaques were challenged with DENV2. All vaccinated macaques were protected from detectable viremia by infectious assay, while naïve animals had detectable viremia for 2–7 days post-challenge. All naïve macaques had detectable viral RNA from day 2–10 post-challenge. In the EDIII-E2 group, three macaques were negative for viral RNA and three were found to have detectable viral RNA post challenge. Viremia onset was delayed and the duration was shortened relative to naïve controls. The presence of viral RNA post-challenge corresponded to a 10–30-fold boost in neutralization titers 28 days post challenge, whereas no boost was observed in the fully protected animals. Based on these results, we determine that pre-challenge 50% neutralization titers of >1:6000 correlated with sterilizing protection against DENV2 challenge in EDIII-E2 vaccinated macaques. Identification of the critical correlate of protection for the EDIII-E2 platform in the robust non-human primate model lays the groundwork for further development of a tetravalent EDIII-E2 dengue vaccine.